Cytotoxic and anti-inflammatory active phloroglucinol derivatives from Rhodomyrtus tomentosa. (September 2018) - Zhang, Yu-Bo; Li, Wen; Jiang, Lin; Yang, Li; Chen, Neng-Hua; Wu, Zhong-Nan; Li, Yao-Lan; Wang, Guo-Cai
Abstract: Seven undescribed phloroglucinol derivatives, tomentodiones N−T, and eleven known ones were isolated from Rhodomyrtus tomentosa . Tomentodione N is the first example of a β -triketone unit coupled with an isoamyl alcohol through a furan fused-ring, and tomentodiones N, S, T were three racemates. The undescribed structures were elucidated by means of spectroscopic, X-ray diffraction, electronic circular dichroism calculation, and chemical methods. In addition, the isolated compounds were determined for the cytotoxic activities on HeLa cells and anti-inflammatory activities in LPS-stimulated RAW 264.7 cells. Graphical abstract: Seven previously undescribed phloroglucinol derivatives and eleven known ones were isolated from Rhodomyrtus tomentosa and their anti-inflammatory and cytotoxic activities were also discussed. Highlights: Eighteen phloroglucinol derivatives were isolated and identified. Seven undescribed compounds were obtained and their structures were elucidated. All the isolates were tested for the cytotoxic and anti-inflammatory activities. Some of the isolates showed pronounced cytotoxic and anti-inflammatory activities.